Arzela-Ascoli Theorem for Demi-Linear Mappings. (2nd March 2014) - Lei, Qiang; Chen, Aihong
Abstract : The Arzela-Ascoli theorem for demi-linear mappings is established. Some conclusions about preserving totally bounded sets are also obtained.